2D velocity vector profile measurement on bubbly flow using ultrasonic technique - Wongsakorn WONGSAROJ (The Japan Society of Mechanical Engineers, 2020)
This paper describes a measurement technique for a two-dimensional (2D) velocity vector profile in the two-phase bubbly flow. The Ultrasonic Velocity Profiler (UVP) method, which is a nonintrusive technique applicable for real-time measurement, is proposed to simultaneously obtain a 2D velocity vector of the bubble and liquid phase in the bubbly flow. To achieve this aim, transducers with special configuration and developed signal processing is applied to the UVP system to reconstruct and decompose a 2D velocity vector of the bubbles and liquid. To confirm the applicability of the improved UVP, the experiment is conducted on a rectangular bubble column flow loop. The 2D velocity vector profile measurement in two-phase bubbly flow is performed experimentally and the applicability of the measurement validated by comparison with other methods.